High-yield gross anatomy - Dudek, Ronald W., 1950-; Louis, Thomas (Philadelphia : Wolters Kluwer Health, 2015)
"High-Yield Gross Anatomy addresses many of the recurring clinical themes of the USMLE Step 1. The information presented in this text prepares you to handle not only the clinical vignettes found on the USMLE Step 1, but also the questions concerning basic gross anatomy concepts"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Human anatomy -- Outlines, syllabi, etc; Anatomy -- Outlines; Anatomy -- Outlines